1993
DOI: 10.1080/00207599308247184
|View full text |Cite
|
Sign up to set email alerts
|

Mental Arithmetic: A Componential Analysis of Speed‐of‐Processing Across Monolingual, Weak Bilingual, and Strong Bilingual Adults

Abstract: Two experiments compared rates of solving simple and complex addition and multiplication problems in groups of speakers of French or English in Experiment 1 (n = 35) and Spanish or English in Experiment 2 (n = 84). Subjects were divided into groups of English unilinguals, weak bilinguals, and strong bilinguals according to their performance on a naming task. In both experiments, simple problems consisted of two single‐digit numbers. At least three single‐digit numbers were used for complex problems in Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 23 publications
3
16
0
Order By: Relevance
“…Thus, the fact that our two Chinese groups were fluently bilingual could be a factor in their better simple-arithmetic performance. Geary, Cormier, Goggin, Estrada, and Lunn (1993) found, however, that adults' simple addition and multiplication performance was not affected by degree of bilingualism. Another possible linguistic influence is that Mandarin uses a consistent system for constructing number names (e.g., 12 is ten two and 53 is five ten three), whereas English is more irregular (e.g., the teens words are quite idiosyncratic).…”
Section: Other Potential Sourcesmentioning
confidence: 65%
“…Thus, the fact that our two Chinese groups were fluently bilingual could be a factor in their better simple-arithmetic performance. Geary, Cormier, Goggin, Estrada, and Lunn (1993) found, however, that adults' simple addition and multiplication performance was not affected by degree of bilingualism. Another possible linguistic influence is that Mandarin uses a consistent system for constructing number names (e.g., 12 is ten two and 53 is five ten three), whereas English is more irregular (e.g., the teens words are quite idiosyncratic).…”
Section: Other Potential Sourcesmentioning
confidence: 65%
“…Previous arithmetic research involving bilinguals has produced mixed conclusions about the role of language in number-fact memory. Geary, Cormier, Goggin, Estrada, and Lunn (1993) found that simple addition and multiplication performance was not affected by degree of bilingualism, which led them to suggest that basic arithmetic facts might be stored in a single-abstract format. Nonetheless, speed of arithmetic in bilinguals is faster when problems are encoded or answers are produced in the preferred language (Frenck-Mestre & Vaid, 1993;Marsh & Maki, 1976;McClain & Shih Huang, 1982).…”
Section: Language and Arithmeticmentioning
confidence: 99%
“…Here, we based our current experiment on previous work in complex arithmetic that showed that both adults and children had poorer performance on harder than on easier problems, whether difficulty of problems was defined on the basis of the size of operands, on involving carryover, or both (e.g., De Smedt, Holloway, & Ansari, 2011;Geary, Cormier, Goggin, Estrada, & Lunn, 1993;Geary, Widaman, Little, & Cormier, 1987;Green, Lemaire, & Dufau, 2007;Hodzik & Lemaire, 2011;Lemaire & Arnaud, 2008;Lemaire & Calliès, 2009;Widaman, Geary, Cormier, & Little, 1989). The present work aimed at replicating such problem difficulty effects on children's performance in complex arithmetic and at testing interactions of problem difficulty with other variables (i.e., children's age and strategies).…”
mentioning
confidence: 99%